Al-Naẓariyyah al-Sulūkiyyah fī Taʿlīm al-Lughah (Dirāsat Waṣf wa Taḥlīl li al-Sulūkiyyah fī al-Ṭarīqah al-Mubāshirah fī Taʿlīm al-Lughah) - Fairuz Subakir Ahmad (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Language learning is a process of acquiring and mastering phonological, grammatical, and lexical patterns in order to achieve effective linguistic performance. From a behaviorist perspective, language learning is viewed as the formation of new habits through responses to environmental stimuli. Accordingly, language instruction involves observable human behavior, including speech production and other physical actions, which are shaped through stimulus–response interactions. Various language teaching methods have been developed to accommodate learners’ behavioral characteristics, each incorporating behaviorist principles in the presentation of instructional materials and classroom practices. This article examines the application of behaviorist theory in language teaching, with particular emphasis on the Direct Method. The study analyzes the behaviorist elements embedded in this method, including its emphasis on speaking skills, direct association between words and their meanings, and the use of dialogue and narrative as instructional techniques. The analysis demonstrates that the Direct Method is fundamentally based on the inseparable relationship between stimulus and response. Furthermore, the study identifies several limitations of this approach and discusses their implications for improving language teaching methodologies, instructional strategies, and curriculum development.